Phytochemical, antioxidant, and in-silico studies of Erigeron sumatrensis from Gayo Highlands as a potential inhibitor of Type-2 diabetes mellitus - VIVERA RUSELLI PUSPA; ZUMAIDAR ZUMAIDAR; NURDIN NURDIN; FITMAWATI FITMAWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Puspa VR, Zumaidar, Nurdin, Fitmawati. 2024. Phytochemical, antioxidant, and in-silico studies of Erigeron sumatrensis from Gayo Highlands as a potential inhibitor of type-2 diabetes mellitus. Biodiversitas 25: 3179-3192. Erigeron sumatrensis Retz., a wild medicinal herb, was determined qualitatively and quantitatively for its leaf extract's phytochemical constituents and antioxidant capacity and to conduct computational studies. Secondary metabolites identified included flavonoids, phenolics, terpenoids, steroids, and alkaloids. The methanol fraction exhibited the greatest TPC (5945.45 mg GAE/g). Antioxidant activity, as determined by the ABTS assay, indicated a significant radical scavenging activity in the methanol fraction of E. sumatrensis leaves, with an IC50 value of 57.67 ?g/mL. In silico molecular docking revealed that cucurbitacin b, 25-desacetoxy-?-sitosterol, and ?-amyrin exhibited potential as ?-glucosidase inhibitors (PDB ID: 2QMJ). The same compounds demonstrated inhibitory properties against ?-amylase (PDB ID: 2QV4), with acarbose as a positive control with a binding energy of -7.8 kcal/mol. The ADMET profiles indicated compliance with Lipinski's rule of five for all compounds, suggesting their suitability as an orally administered drug. Based on these findings, E. sumatrensis has excellent potential as a source of raw materials for antidiabetic drug formulation, so it needs to be further investigated for pharmaceutical applications.